A Systematic and Critical Review of Parental Program Integrated to Prevent and Manage Delay Development in Children - Rian Adi Pamungkas; Kanittha Chamroonsawasdi; Andi Mayasari Usman; Widia Sari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Delay development is a crucial problem in the early childhood period. An effective parental program is an essential strategy to prevent and manage delayed development. However, limited number studies described how parental integrated to prevent and manage delay development systematically. This review aims to describe developmental delays and explore strategies for their prevention and management in early childhood. Method: A total of 1,237 articles were extracted from four databases including, PubMed, Scopus, and Web of Science, using suitable keywords as;